2006
DOI: 10.1007/s10562-005-9736-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water on the Activity and Selectivity for γ-Alumina Supported Cobalt Fischer–Tropsch Catalysts with Different Pore Sizes

Abstract: The effect of water on the activity and selectivity for a series of c-Al 2 O 3 supported cobalt Fischer-Tropsch catalysts has been studied in an isothermal fixed-bed reactor at T=483 K, P=20 bar, and H 2 /CO=2.1. The catalysts were produced applying incipient wetness impregnation and consisted of 20 wt.% cobalt and 0.5 wt.% rhenium deposited on c-Al 2 O 3 supports with different pore characteristics. For the narrow-pore catalysts, addition of water corresponding to an inlet partial pressure ratio of P H2 O/P H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 38 publications
10
40
0
Order By: Relevance
“…Water is one of the major products of FT synthesis. The decrease in the FT reaction rate is usually attributed to catalyst deactivation due to sintering of the cobalt, and segregation of the noble meal promoter, oxidation of the cobalt surface or small cobalt clusters [39][40][41][42]. The introduction of noble metal could increase the extent of reduction by dissociating hydrogen which then spills over to reduce the cobalt oxide to cobalt metal.…”
Section: Catalytic Performances Of Carbon Nanoble Supported Bimetal Cmentioning
confidence: 99%
“…Water is one of the major products of FT synthesis. The decrease in the FT reaction rate is usually attributed to catalyst deactivation due to sintering of the cobalt, and segregation of the noble meal promoter, oxidation of the cobalt surface or small cobalt clusters [39][40][41][42]. The introduction of noble metal could increase the extent of reduction by dissociating hydrogen which then spills over to reduce the cobalt oxide to cobalt metal.…”
Section: Catalytic Performances Of Carbon Nanoble Supported Bimetal Cmentioning
confidence: 99%
“…2 that all catalysts show a two-step reduction for cobalt oxides: a first peak (peak I) at 442-589 K, ascribed to reduction of Co 3 O 4 to CoO, is followed by a second peak (peak II) at around 622-728 K (less marked for the CoSBA-15 catalyst) corresponding to the reduction of CoO to Co [13,14]. CoSBA-15 shows a more complex profile with a broad H 2 -uptake at temperatures between 600 and 1,200 K, suggesting the presence of surface cobalt species with different degrees of interaction with the support [13,14]. It has also been reported that in the 1-D porous structure (with narrow pores), the slow removal of water formed upon reduction may affect the appearance of the TPR, and even promote the formation of barely reducible cobalt silicates [15,16].…”
Section: Fischer-tropsch Synthesismentioning
confidence: 89%
“…It can be seen from Fig. 2 that all catalysts show a two-step reduction for cobalt oxides: a first peak (peak I) at 442-589 K, ascribed to reduction of Co 3 O 4 to CoO, is followed by a second peak (peak II) at around 622-728 K (less marked for the CoSBA-15 catalyst) corresponding to the reduction of CoO to Co [13,14]. CoSBA-15 shows a more complex profile with a broad H 2 -uptake at temperatures between 600 and 1,200 K, suggesting the presence of surface cobalt species with different degrees of interaction with the support [13,14].…”
Section: Fischer-tropsch Synthesismentioning
confidence: 97%
“…Water contributed to the sintering and thus caused the deactivation of the catalyst. Still, neither cobalt loss nor the surface compound formation between cobalt and zirconia was detected [13].…”
Section: Introductionmentioning
confidence: 89%
“…In turn, the proposed monomer dependencies in the F-T synthesis mechanism explain the lower methane selectivity and higher molecular weight products observed at increased water concentrations. The deactivation of coprecipitated Co-ZrO 2 catalyst during F-T synthesis was investigated in a fixed-bed reactor under dry and water addition conditions [13]. It was found that the activity of the catalyst decreased after reaction and the catalyst deactivated more with water addition during reaction.…”
Section: Introductionmentioning
confidence: 99%